2006
DOI: 10.1002/adma.200502453
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of a Superhydrophobic Surface from the Amplified Exponential Growth of a Multilayer

Abstract: Superhydrophobic surfaces have received much attention due to their novel aspects of surface physics and important applications ranging from self-cleaning materials to microfluidic devices. Taking their inspiration from the self-cleaning property of lotus leaves [1] and insects, [2] the biomimetic results reveal that the synergistic interaction of the hierarchical micro-and nanostructure can not only improve the surface hydrophobicity but also reduce the sliding angle (SA), which is crucial to the self-clean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
114
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(122 citation statements)
references
References 49 publications
5
114
0
1
Order By: Relevance
“…It seems that the initial three polyelectrolyte layers on the CEM were thicker than the subsequent layers. This is not in accordance with early studies 29,30 that the PEI/PAA multilayer films grow exponentially in the first several bilayers. We believe it was mainly due to the different substrates for polyelectrolyte adsorption.…”
Section: Effect Of the Bilayer Number On Separation Performance And Rsupporting
confidence: 46%
“…It seems that the initial three polyelectrolyte layers on the CEM were thicker than the subsequent layers. This is not in accordance with early studies 29,30 that the PEI/PAA multilayer films grow exponentially in the first several bilayers. We believe it was mainly due to the different substrates for polyelectrolyte adsorption.…”
Section: Effect Of the Bilayer Number On Separation Performance And Rsupporting
confidence: 46%
“…[39] In addition, the growth can be amplified by pH leading to even thicker films obtained in a very limited number of depositing cycles. [40] Better understanding of the different growth mechanisms is also emerging. [12] For instance, Porcel et al [41] showed that a transition from exponential to linear growth occurs at a certain level in film buildup.…”
Section: Growth Mode: Linear Versus Exponentialmentioning
confidence: 99%
“…[221] Superhydrophobic surfaces also attract lots of attention and are inspired by the natural designs of the Lotus leaf or insect wings. Ji et al [40] prepared superhydrophobic films using films that grow exponentially with growth that was amplified due to the presence of silver ions. Other strategies rely on organic-inorganic hybrid films, such as PAH and ZrO 2 nanoparticle coatings, [222] in combination with the LbL technique with electrochemical depositing of dendritic gold aggregate coatings on gold threads, [223] or on a polyelectrolyte/sodium silicate combination.…”
Section: Mimicking the Properties Of Natural Materialsmentioning
confidence: 99%
“…[51][52][53][54] In the work reported here, polyelectrolyte multilayers (PEMs) with hierarchical nano-and microscale surface structures were constructed of poly(acrylic acid) (PAA) and polyethyleneimine (PEI), [12] which show an exponential growth mode. [55,56] To speed up preparation and to move towards future practical application, spray coating was used for the layer-by-layer application. [57,58] The pH of the applied polyelectrolyte solutions was tuned to obtain morphologies with systematically varying structure sizes.…”
mentioning
confidence: 99%